Forsterite-polytetrafluoroethylene composite material as well as preparation method and application thereof

By adding grease to the spherical silicon-containing powder and mixing it with magnesium powder, co-condensation with PTFE after sintering, a uniform magnesium-PTFE composite material was prepared, and the ceramic-filled polytetrafluoroethylene microwave composite media substrate process was solved. The problems of complexity and insufficient dielectric performance achieve efficient and uniform dielectric performance and large-scale production.

CN119264584AActive Publication Date: 2025-01-07SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411314544.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-07
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing ceramic-filled polytetrafluoroethylene microwave composite dielectric substrate preparation process is complex and has poor practicality, making it difficult to achieve full combination of ceramic powder and PTFE, resulting in poor film thickness and film uniformity, and dielectric performance needs to be improved.

Method used

The oil is added dropwise to the spherical silicon-containing powder for infiltration to form a gel-like mixture, and then the magnesium-containing powder is added and sintered to obtain spherical magnesium-sterilite, which is then co-coagulated with the PTFE emulsion to coat the magnesium-sterilite. Thus, a uniform forsterite-PTFE composite material was prepared.

Benefits of technology

The process flow is simplified, the uniformity and dielectric properties of forsterite-PTFE composite materials are improved, the cost is reduced, and the efficient large-scale production is achieved, which is suitable for high-frequency and high-speed signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264584A_ABST
    Figure CN119264584A_ABST
Patent Text Reader

Abstract

The invention discloses a forsterite-polytetrafluoroethylene composite material as well as a preparation method and application thereof, and the preparation method of the forsterite-polytetrafluoroethylene composite material comprises the following steps: dropwise adding grease into spherical silicon-containing powder, and infiltrating the silicon-containing powder until a colloidal mixture is formed; adding magnesium-containing powder into the colloidal mixture and mixing to obtain a spherical forsterite precursor; the forsterite precursor is sintered, and spherical forsterite is obtained; the forsterite and the polytetrafluoroethylene emulsion are subjected to co-condensation, so that the surface of the forsterite is coated with polytetrafluoroethylene, and the forsterite-polytetrafluoroethylene composite material is obtained. The forsterite-polytetrafluoroethylene composite material prepared in the invention has good uniformity and dielectric properties, is suitable for preparation of copper-clad plates and printed circuit boards in the 5G field, can meet high-frequency and high-speed signal transmission, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a forsterite-polytetrafluoroethylene composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of millimeter-wave high-frequency applications, higher requirements are placed on high-frequency and high-speed signal transmission. Traditional circuit substrates cannot meet the requirements of 5G communications. Therefore, the development of a low-cost, high-performance, high-stability high-frequency, high-speed microwave composite dielectric substrate is particularly important. Microwave composite dielectric substrates with low dielectric constants are very beneficial for high-speed, low-latency, and lossless transmission of microwave signals, making them widely used in ultra-high density and ultra-large-scale integrated circuits. Polytetrafluoroethylene has become one of the main substrate materials in the field of radio frequency microwaves due to its ultra-low dielectric constant and dielectric loss. In order to further improve the comprehensive performance of the substrate, most of the materials of microwave composite dielectric substrates are currently made of ceramic-filled polytetrafluoroethylene (PTFE).

[0003] However, the existing preparation method of ceramic-filled polytetrafluoroethylene is complex and has poor practicality. It is still in the laboratory research stage and difficult to apply industrially. In addition, in order to achieve a full combination of ceramic powder and PTFE, it is usually necessary to use coupling agent coating or other additives to modify the surface of the ceramic powder, which further increases the complexity of the process. In addition, the film thickness and uniformity of the film layer of the microwave composite dielectric substrate prepared by the current method are poor, and the dielectric properties need to be improved. Summary of the invention

[0004] In view of this, the present application provides a method for preparing a forsterite-polytetrafluoroethylene (PTFE) composite material, which can improve the uniformity and dielectric properties of the forsterite-PTFE composite material.

[0005] In addition, the present application also provides a forsterite-PTFE composite material prepared by the aforementioned preparation method, and a copper-clad laminate and a printed circuit board using the forsterite-PTFE composite material.

[0006] The present invention provides a method for preparing a forsterite-PTFE composite material, comprising the following steps:

[0007] Adding grease dropwise into the spherical silicon-containing powder to wet the silicon-containing powder until a gelatinous mixture is formed;

[0008] adding magnesium-containing powder to the colloidal mixture and mixing to obtain a spherical forsterite precursor;

[0009] Sintering the forsterite precursor to obtain spherical forsterite; and

[0010] The forsterite and PTFE emulsion are co-coagulated to coat the surface of the forsterite with PTFE, thereby obtaining the forsterite-PTFE composite material.

[0011] In some possible embodiments, in the colloidal mixture, the mass fraction of the oil is 15% to 30%, and the mass fraction of the silicon-containing powder is 70% to 85%.

[0012] In some possible embodiments, the molar ratio of the magnesium-containing powder to the silicon-containing powder is (1.5-2.3):1.

[0013] In some possible embodiments, the mass ratio of the forsterite to the PTFE in the PTFE emulsion is 1:(0.43-1).

[0014] In some possible embodiments, the sintering temperature is 800° C. to 1100° C., and the sintering time is 2 h to 8 h.

[0015] In some possible embodiments, the oil includes at least one of dibutyl phthalate, liquid paraffin, petroleum ether, toluene, xylene, diethyl phthalate, dibenzyl phthalate, diisooctyl phthalate and diphenyl phthalate.

[0016] In some possible embodiments, the silicon-containing powder includes at least one of silicon powder, silicate and silicon oxide;

[0017] The magnesium-containing powder includes at least one of magnesium hydroxide, magnesium oxide, magnesium chloride and magnesium sulfate.

[0018] The embodiment of the present application also provides a forsterite-PTFE composite material, and the forsterite-PTFE composite material is prepared by the aforementioned preparation method.

[0019] The embodiment of the present application further provides a copper-clad laminate, which includes a substrate and a metal layer located on the surface of the substrate, and the substrate is made of the forsterite-PTFE composite material mentioned above.

[0020] An embodiment of the present application further provides a printed circuit board, which includes a substrate and a circuit layer located on the surface of the substrate, wherein the substrate is made of the forsterite-PTFE composite material.

[0021] Compared to the prior art, the preparation method of the forsterite-PTFE composite material provided in the embodiment of the present application, by first dripping grease into the spherical silicon-containing powder, semi-plasticizing the silicon-containing powder, and then mixing with magnesium-containing powder, this novel step-by-step mixing method effectively improves the mixing effect of silicon-containing powder and magnesium-containing powder, and is conducive to obtaining spherical forsterite with uniform morphology and less surface defects, thereby improving the compatibility of forsterite and PTFE, so that the prepared forsterite-PTFE composite material has a more uniform structure and interface, and the spherical forsterite of the preparation method can be directly co-coagulated with PTFE, without the need to modify the surface of forsterite or add auxiliary agents, reducing the influence of additives such as auxiliary agents on the performance of forsterite-PTFE composite materials, and the uniformity of the forsterite-PTFE composite material obtained is better, and it has excellent dielectric properties. The preparation method is simple in process, strong in practicality, high in efficiency, and low in cost, and can achieve continuous large-scale production of forsterite-PTFE composite materials. The copper clad laminate prepared using the forsterite-PTFE composite material provided in the embodiment of the present application has a lower dielectric constant and dielectric loss, and the prepared printed circuit board has excellent performance, is stable and reliable, and can meet the requirements of high-frequency and high-speed signal transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process flow chart of the preparation method of the forsterite-polytetrafluoroethylene composite material provided in the embodiment of the present application.

[0023] Figure 2 This is a scanning electron microscope image of forsterite in Example 1 of the present application.

[0024] Figure 3 This is a scanning electron microscope image of the forsterite-polytetrafluoroethylene composite material in Example 1 of the present application.

[0025] Figure 4 This is a scanning electron microscope image of the forsterite-polytetrafluoroethylene composite material in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0027] See also Figure 1 As shown, the preparation method of the forsterite-polytetrafluoroethylene (PTFE) composite material provided in the embodiment of the present application specifically includes the following steps:

[0028] Step S1, adding grease dropwise into spherical silicon-containing powder to wet the silicon-containing powder until a gelatinous mixture is formed.

[0029] Step S2, adding magnesium-containing powder to the colloidal mixture and mixing, to obtain a spherical forsterite precursor.

[0030] Step S3, sintering the forsterite precursor to obtain spherical forsterite.

[0031] Step S4, co-coagulating forsterite and PTFE emulsion to coat the surface of forsterite with PTFE, thereby obtaining a forsterite-PTFE composite material.

[0032] In step S1: gradually drip grease into the spherical silicon-containing powder, so that the grease completely infiltrates the silicon-containing powder until a viscous colloid is formed, thereby semi-plasticizing the silicon-containing powder. When the grease is mixed with the silicon-containing powder, the grease molecules can form a lubricating film between the silicon-containing powders, which is beneficial to reduce the surface energy of the silicon-containing powder, making it easier for the silicon-containing powder to undergo relative displacement during processing, thereby increasing the plasticity of the silicon-containing powder, which is beneficial for uniform mixing with the magnesium-containing powder in step S2. Among them, the silicon-containing powder is a spherical silicon-containing powder, which has better fluidity and can be uniformly mixed with the magnesium-containing powder, and the use of spherical silicon-containing powder can make the subsequently prepared forsterite also spherical.

[0033] Before the step of soaking the silicon-containing powder with grease, the preparation method may further include: drying the silicon-containing powder, the drying temperature may be 100° C. to 140° C., and the drying time may be 10 hours to 24 hours. The drying pretreatment of the silicon-containing powder is intended to remove moisture and volatile substances in the silicon-containing powder and improve the stability and processability of the silicon-containing powder.

[0034] In step S1, in the colloidal mixture, the mass fraction of the grease may be 15% to 30%, further may be 20% to 30%, illustratively, the mass fraction of the grease may be 15%, 18%, 20%, 22%, 25%, 28% or 30%, etc. The mass fraction of the silicon-containing powder may be 70% to 85%, further may be 70% to 80%, illustratively, the mass fraction of the silicon-containing powder may be 70%, 75%, 78%, 80%, 82%, 84% or 85%, etc. The appropriate mixing ratio of grease and silicon-containing powder can further improve the surface modification effect while maintaining the desired silicon-containing powder content and processing performance.

[0035] In step S1, the silicon-containing powder may include at least one of silicon micropowder, silicate and silicon oxide. The above silicon-containing powders all have certain advantages such as thermal stability, chemical stability, mechanical strength or low cost and availability. Selecting the above silicon-containing powder material to fill polytetrafluoroethylene is conducive to further making polytetrafluoroethylene have excellent dielectric properties and mechanical properties. The silicon-containing powder can be exemplarily silicon micropowder or silicon dioxide.

[0036] In step S1, the particle size D50 of the silicon-containing powder can be 4 μm to 16 μm. The silicon-containing powder within this particle size range can more easily form a uniform colloidal mixture when mixed with oil, which helps to form a spherical and uniform forsterite precursor, thereby improving the sphericity and performance of forsterite. The particle size D50 of the silicon-containing powder can further be 6 μm to 12 μm, and can be 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm or 16 μm, etc.

[0037] In step S1, the oil may include at least one of dibutyl phthalate, liquid paraffin, petroleum ether, toluene, xylene, diethyl phthalate, dibenzyl phthalate, diisooctyl phthalate and diphenyl phthalate, etc. The oils in the above range can semi-plasticize the silicon-containing powder well.

[0038] In step S2: magnesium-containing powder is added to the colloidal mixture of silicon-containing powder and grease and mixed, and the two are fully mixed into a dough-like state to obtain a spherical forsterite precursor. Since the silicon-containing powder has become a semi-plastic fluid under the action of the grease, it is beneficial for the magnesium-containing powder to be evenly mixed in the colloidal mixture, thereby improving the spheroidization degree of forsterite, avoiding the appearance of forsterite with a structure such as flaky or polygonal, and finally obtaining a spherical forsterite precursor with good uniformity.

[0039] In step S2, a sintering aid may be added and mixed together. The sintering aid may include at least one of lithium fluoride, sodium fluoride, and aluminum fluoride. The sintering aid may effectively reduce the sintering temperature of the forsterite precursor and improve the sintering density. The mass fraction of the sintering aid in the forsterite precursor may be 0.8% to 2%, which can reduce the sintering temperature and improve the sintering density.

[0040] The molar ratio of the magnesium-containing powder added in step S2 to the silicon-containing powder in step S1 can be (1.5-2.3):1, and the above molar ratio range is conducive to the reaction to form forsterite (Mg2SiO4). The molar ratio can further be (2-2.3):1, and can be exemplarily 1.5:1, 1.8:1, 2:1, 2.1:1, 2.2:1 or 2.3:1, etc.

[0041] In step S2, the magnesium-containing powder may include at least one of magnesium hydroxide, magnesium oxide, magnesium chloride, magnesium sulfate, etc., and illustratively may be magnesium hydroxide.

[0042] In step S3: the forsterite precursor is sintered to obtain spherical forsterite. Since the forsterite precursor has good consistency and each component is evenly distributed, the obtained forsterite has a uniform morphology.

[0043] Since spherical silicon-containing powder is used in step S1, and under the effect of oil infiltration, the silicon-containing powder and the magnesium-containing powder are dispersed more evenly and can fully contact each other, thereby forming spherical forsterite with better surface morphology. Forsterite with such a spherical structure has many advantages, including: (1) good fluidity, because the friction of the spherical shape is smaller than that of the irregularly shaped forsterite, it is easier to mix with PTFE in the subsequent process; (2) improved sintering performance, the spherical particles can contact and fuse more evenly during the high-temperature sintering process, which helps to reduce sintering defects and thus form a uniform structure; (3) uniform distribution, the spherical forsterite particles can be more evenly distributed in PTFE during the co-coagulation process, reducing the particle aggregation phenomenon, which is crucial for the subsequent molding process and can ensure the quality and consistency of the final product; (4) high density and high strength, the spherical particles help to form a denser composite material structure, thereby improving the wear resistance and corrosion resistance of the forsterite-PTFE composite material.

[0044] In step S3, the heating rate of sintering can be 2°C / min to 5°C / min, the sintering temperature can be 800°C to 1100°C, and the sintering time can be 2h to 8h. The forsterite precursor is uniformly heated to ensure sufficient sintering to form the desired forsterite.

[0045] In step S4: forsterite is fully dispersed in the solvent, then PTFE emulsion is added to mix and co-coagulation is carried out, PTFE is coated on the surface of forsterite, then the co-coagulation product is carried out solid-liquid separation and the co-coagulation product (solid powder) is dried to obtain forsterite-PTFE composite material. Wherein, spherical forsterite and PTFE emulsion have good compatibility, can realize the uniform mixing of forsterite and PTFE without the need to carry out surface modification to forsterite or adding auxiliary agent, complete co-coagulation, greatly reduce the impact of coupling agent or other auxiliary agents on product performance. Simultaneously because forsterite and PTFE have good compatibility, PTFE can evenly coat forsterite, thus the forsterite-PTFE composite material made has more uniform structure and interface, improves the dielectric properties and the homogeneity of forsterite-PTFE composite material.

[0046] In step S4, the mass ratio of forsterite to the solvent may be 1:(3-6), which is conducive to the full dispersion of forsterite in the solution. The mass ratio of forsterite to the solution may further be 1:(4-5), and may be 1:3, 1:3.5, 1:4, 1:4.5, 1:4.6, 1:5, 1:5.5 or 1:6, etc.

[0047] In step S4, the mass ratio of forsterite to PTFE in the PTFE emulsion can be 1:(0.43-1), and can further be 1:(0.5-0.6), and can exemplarily be 1:0.43, 1:0.45, 1:0.5, 1:0.54, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc., which is conducive to further meeting the performance requirements of forsterite-PTFE composite materials.

[0048] In step S4, the solvent may be water, and may further be deionized water, which can effectively reduce interference from impurities and improve the quality of the forsterite-PTFE composite material.

[0049] Compared with the prior art, the preparation method of the forsterite-PTFE composite material provided in the embodiment of the present application has the following beneficial effects:

[0050] 1. The step-by-step mixing method is adopted to drip grease into silicon-containing powder, semi-plasticize the silicon-containing powder, and then add magnesium-containing powder and mix thoroughly. The step-by-step mixing method prepares spherical forsterite with good morphology, thereby improving the compatibility of forsterite and PTFE, improving the dielectric properties and uniformity of forsterite-PTFE composite materials, and the mixing method has excellent uniformity and stability. At the same time, the mixing method provides a new and efficient solution for the preparation of composite dielectric substrate materials, which is conducive to the large-scale production of forsterite-PTFE composite materials.

[0051] 2. The process flow is simplified and the performance of subsequent products is improved. Forsterite can be directly co-coagulated with PTFE without additional surface modification of the forsterite or addition of additives, thereby reducing the impact of additional additives on the performance of subsequent products. The preparation process of the forsterite-PTFE composite material of the present application is simple, and the obtained forsterite-PTFE composite material has excellent performance.

[0052] The embodiment of the present application provides a forsterite-PTFE composite material, which is prepared by the preparation method as described above. Compared with the prior art, the forsterite-PTFE composite material provided in the embodiment of the present application has excellent dielectric properties and uniformity, which is conducive to the forsterite-PTFE composite material being applied to copper-clad laminates and printed circuit boards to maintain stable performance and low dielectric loss during high-frequency and high-speed signal transmission, thereby extending the service life.

[0053] The present application also provides a copper-clad laminate, which includes a substrate and a metal layer on the surface of the substrate, and the substrate is made of the forsterite-PTFE composite material. Compared with the prior art, the copper-clad laminate provided in the present application has a low dielectric constant and low dielectric loss, and can ensure stable and complete transmission of signals for high-speed and high-frequency circuits.

[0054] In some embodiments, before preparing the copper-clad laminate, a certain amount of isoparaffin additive can be further added to the obtained forsterite-PTFE composite material, and the polytetrafluoroethylene composite material after adding the additive is aged at 25°C to 60°C for 1h to 3h. During the aging process, the structure of the forsterite-PTFE composite material gradually stabilizes, and the powder is solidified into a block, which is beneficial to improve the processing performance of the forsterite-PTFE composite material and the stability of subsequent treatment. Among them, the mass ratio of the forsterite-PTFE composite material to the isoparaffin additive is 1: (0.3 to 0.5), and can further be 1: (0.3 to 0.4), and can be exemplarily 1: 0.3, 1: 0.33, 1: 0.4, 1: 0.45 or 1: 0.5, etc.

[0055] The embodiment of the present application also provides a printed circuit board, including a substrate and a circuit layer located on the surface of the substrate, wherein the substrate is made of the aforementioned forsterite-PTFE composite material. Therefore, the printed circuit board can effectively reduce the propagation delay and signal attenuation of the signal, and help maintain the integrity and stability of the signal; it can also effectively reduce the energy loss during the signal transmission process, and ensure the high-speed transmission and accuracy of the signal. Combining the above advantages, the printed circuit board can ensure the stable transmission and complete signal transmission in high-speed and high-frequency circuits, and can meet the increasingly complex and rapidly developing communication and data processing needs.

[0056] The forsterite-PTFE composite material and its preparation method and application are further described below through specific examples.

[0057] Example 1

[0058] Step 1: Place the spherical silicon micropowder in a blast drying oven at 120° C. for 24 hours to remove moisture, soak the dried spherical silicon micropowder with dibutyl phthalate, and mix thoroughly until a colloidal mixture is formed, wherein the mass ratio of dibutyl phthalate to the dried spherical silicon micropowder is 3:7.

[0059] Step 2: Add magnesium hydroxide and lithium fluoride sintering aids to the colloidal mixture and mix them to obtain a forsterite precursor, wherein the molar ratio of microsilica powder to magnesium hydroxide in the slurry is 1:2, and the mass ratio of microsilica powder to lithium fluoride is 1:0.03.

[0060] Step 3: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 800°C for 2 hours to obtain spherical forsterite.

[0061] Step 4, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0062] Step 5, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0063] Example 2

[0064] Step 1: Place the spherical silicon micropowder in a forced air drying oven at 120° C. for 24 hours to remove moisture, soak the dried spherical silicon micropowder with dibutyl phthalate, and mix thoroughly until a colloidal mixture is formed, wherein the mass ratio of dibutyl phthalate to the dried spherical silicon micropowder is 2:8.

[0065] Step 2: Add magnesium hydroxide and lithium fluoride sintering aids to the colloidal mixture and mix them to obtain a forsterite precursor, wherein the molar ratio of microsilica powder to magnesium hydroxide in the slurry is 1:2, and the mass ratio of microsilica powder to lithium fluoride is 1:0.03.

[0066] Step 3: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 800°C for 2 hours to obtain spherical forsterite.

[0067] Step 4, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0068] Step 5, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0069] Example 3

[0070] Step 1: Place the spherical silicon micropowder in a blast drying oven at 120° C. for 24 hours to remove moisture, soak the dried spherical silicon micropowder with dibutyl phthalate, and mix thoroughly until a colloidal mixture is formed, wherein the mass ratio of dibutyl phthalate to the dried spherical silicon micropowder is 3:7.

[0071] Step 2: Add magnesium hydroxide and lithium fluoride sintering aids to the colloidal mixture and mix them to obtain a forsterite precursor, wherein the molar ratio of microsilica powder to magnesium hydroxide in the slurry is 1:2, and the mass ratio of microsilica powder to lithium fluoride is 1:0.03.

[0072] Step 3: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 900°C for 2 hours to obtain spherical forsterite.

[0073] Step 4, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0074] Step 5, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0075] Comparative Example 1

[0076] Step 1, placing the spherical silicon powder in a blast drying oven at 120° C. for 24 hours to remove moisture, adding magnesium hydroxide and lithium fluoride sintering aids to the spherical silicon powder and mixing, to obtain a forsterite precursor, wherein the molar ratio of silicon powder to magnesium hydroxide is 1:2, and the mass ratio of silicon powder to lithium fluoride is 1:0.03.

[0077] Step 2: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 800°C for 2 hours to obtain spherical forsterite.

[0078] Step 3, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0079] Step 4, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0080] Comparative Example 2

[0081] Step 1, placing the spherical silicon powder in a blast drying oven at 120° C. for 24 hours to remove moisture, adding dibutyl phthalate, magnesium hydroxide and lithium fluoride sintering aids to the dried spherical silicon powder and mixing them to obtain a forsterite precursor, wherein the molar ratio of silicon powder to magnesium hydroxide is 1:2, and the mass ratio of dibutyl phthalate, silicon powder and lithium fluoride is 3:7:0.21.

[0082] Step 2: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 800°C for 2 hours to obtain spherical forsterite.

[0083] Step 3, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0084] Step 4, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0085] Comparative Example 3

[0086] Step 1, placing the spherical silicon micropowder in a blast drying oven at 120° C. for 24 hours to remove moisture, adding magnesium hydroxide and lithium fluoride sintering aids to the dried spherical silicon micropowder and mixing to obtain a mixture, wherein the molar ratio of silicon powder to magnesium hydroxide in the mixture is 1:2, and the mass ratio of silicon powder to lithium fluoride is 1:0.03.

[0087] Step 2: adding dibutyl phthalate to the mixture to obtain a forsterite precursor, wherein the mass ratio of dibutyl phthalate to the microsilica powder in the mixture is 3:7.

[0088] Step 3: calcining the forsterite precursor in a muffle furnace at a heating rate of 5°C / min and sintering at 800°C for 2 hours to obtain spherical forsterite.

[0089] Step 4, dispersing the spherical forsterite obtained in step 4 in deionized water, fully dispersing at 1500 rpm for 30 minutes, then adjusting the speed to 500 rpm, adding PTFE emulsion, wherein the mass ratio of spherical forsterite, deionized water and PTFE contained in the PTFE emulsion is 1:5:0.54, co-coagulation is carried out to obtain a co-coagulation complex, the co-coagulation complex is separated from the solid and liquid, and the lower layer of white powder complex is taken and dried at 120°C for 8 hours to obtain a forsterite-PTFE composite material.

[0090] Step 5, adding an isoparaffin additive to the forsterite-PTFE composite material, wherein the mass ratio of the isoparaffin additive to the forsterite-PTFE composite material is 1:3, aging at 60°C for 1 hour to obtain a uniform composite, and then extruding, calendering, laminating, and copper-coated on both sides for high-temperature pressing at 380°C to obtain a spherical forsterite-filled PTFE-based copper-clad laminate.

[0091] 1. The forsterite, forsterite-PTFE composite material (after calendering treatment) in Example 1 and the forsterite-PTFE composite material (after calendering treatment) in Comparative Example 1 were observed by scanning electron microscopy.

[0092] The scanning electron microscope image of the forsterite prepared in Example 1 is as follows Figure 2 As shown by Figure 2 It can be seen that the forsterite prepared in Example 1 is spherical, which is conducive to more uniform mixing with PTFE. The microscopic morphology of the forsterite-PTFE composite material (after calendering treatment) prepared in Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that PTFE uniformly wraps forsterite with good uniformity. This is because the addition of oil improves the plasticity of silicon powder, thereby improving the surface hydrophobicity of spherical forsterite, achieving uniform coating of PTFE on forsterite and ensuring good bonding between the two, which is conducive to obtaining forsterite-PTFE composite materials with excellent uniformity. The microscopic morphology of the forsterite-PTFE composite material (after calendering treatment) in Comparative Example 1 is shown in FIG. Figure 4 As shown, PTFE cannot uniformly coat forsterite, and the forsterite-PTFE composite material has poor uniformity.

[0093] 2. The dielectric properties of the forsterite of Examples 1-3 and Comparative Examples 1-3 and the copper-clad laminate with the surface copper foil etched away were tested. The results are shown in Table 1.

[0094] (1) Dielectric property test of forsterite: A cavity resonator fixture for measuring frequency of 10 GHz was used, and a powder sample was filled in a sample tube made of PTFE, and then measured by a vector network analyzer.

[0095] (2) Dielectric property test of copper clad laminate: The dielectric property is tested by using the separated cylindrical resonant cavity method (a standard of the American Society for Testing and Materials, method number ASTM2520). First, prepare a 10 GHz test fixture and connect the fixture to the network analyzer. First, measure the center frequency f of the cavity. c And the quality factor Q c , then insert the sample and measure the center frequency f again after loading the sample s And the loaded quality factor Q s . Then the dielectric constant and loss are calculated using the following formula:

[0096]

[0097] Among them, f c is the center frequency of the cavity, f s is the center frequency of the sample, Q cis the cavity quality factor, Q s is the sample quality factor, V c is the volume of the cavity, V s is the volume of the sample.

[0098] Table 1

[0099]

[0100] The results show that compared with the forsterite prepared in Comparative Examples 1-3, the forsterite prepared in Examples 1-3 exhibits lower dielectric loss. This is because the mixing method adopted in the examples is step-by-step mixing, that is, the silicon-containing powder is first soaked in grease, and then the magnesium-containing powder is added, so that the silicon-containing powder and the magnesium-containing powder are mixed more evenly, which helps the forsterite to form a more uniform spherical structure, and the spherical structure has good surface properties, thereby improving the dielectric properties of the forsterite.

[0101] Compared with the copper clad laminates in comparative examples 1-3, the copper clad laminates in examples 1-3 exhibit lower dielectric constants and dielectric losses, which indicates that the copper clad laminates provided in the examples of the present application have excellent dielectric properties.

[0102] Specifically analyzed, in comparative example 1, silicon micropowder and magnesium-containing powder are directly mixed, and grease is not added, so that the forsterite prepared cannot be evenly mixed with PTFE, resulting in poor dielectric properties after etching the surface copper foil of the copper-clad laminate obtained; in comparative example 2, grease, silicon-containing powder and magnesium-containing powder are mixed in one step, and grease fails to fully play a role in modifying silicon-containing powder, and compared with the step-by-step mixing of Examples 1-3, the dielectric properties of the copper-clad laminate obtained are reduced; in comparative example 3, silicon-containing powder and magnesium-containing powder are pre-mixed, and then grease is added to mix, and due to the change in the mixing method, silicon-containing powder and magnesium-containing powder have already been unevenly combined in the initial stage, and the grease added later cannot effectively achieve the semi-plasticization of silicon micropowder and the treatment of hydrophobic modification. The forsterite obtained in 1-3 in comparative example has poor uniformity, and even part of forsterite is non-spherical, causing subsequent polytetrafluoroethylene to be unable to evenly wrap forsterite, and the uniformity of the forsterite-PTFE composite obtained is poor, thereby affecting the dielectric properties of the copper-clad laminate.

[0103] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a forsterite-polytetrafluoroethylene composite material, characterized in that: include: Adding grease dropwise into the spherical silicon-containing powder to wet the silicon-containing powder until a gelatinous mixture is formed; adding magnesium-containing powder to the colloidal mixture and mixing to obtain a spherical forsterite precursor; Sintering the forsterite precursor to obtain spherical forsterite; as well as The forsterite and polytetrafluoroethylene emulsion are co-coagulated to coat the surface of the forsterite with polytetrafluoroethylene, thereby obtaining the forsterite-polytetrafluoroethylene composite material.

2. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: In the colloidal mixture, the mass fraction of the oil is 15% to 30%, and the mass fraction of the silicon-containing powder is 70% to 85%.

3. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: The molar ratio of the magnesium-containing powder to the silicon-containing powder is (1.5-2.3):

1.

4. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: The mass ratio of the forsterite to the polytetrafluoroethylene in the polytetrafluoroethylene emulsion is 1:(0.43-1).

5. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: The sintering temperature is 800° C. to 1100° C., and the sintering time is 2 h to 8 h.

6. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: The oil comprises at least one of dibutyl phthalate, liquid paraffin, petroleum ether, toluene, xylene, diethyl phthalate, dibenzyl phthalate, diisooctyl phthalate and diphenyl phthalate.

7. The method for preparing the forsterite-polytetrafluoroethylene composite material according to claim 1, characterized in that: The silicon-containing powder includes at least one of silicon powder, silicate and silicon oxide; The magnesium-containing powder includes at least one of magnesium hydroxide, magnesium oxide, magnesium chloride and magnesium sulfate.

8. A forsterite-polytetrafluoroethylene composite material, characterized in that: The composite material is prepared by the method for preparing the forsterite-polytetrafluoroethylene composite material according to any one of claims 1 to 7.

9. A copper clad laminate, characterized in that: It comprises a substrate and a metal layer located on the surface of the substrate, wherein the substrate is made of the forsterite-polytetrafluoroethylene composite material as claimed in claim 8.

10. A printed circuit board, characterized in that: It comprises a substrate and a circuit layer located on the surface of the substrate, wherein the substrate is made of the forsterite-polytetrafluoroethylene composite material as claimed in claim 8.

Citation Information

Patent Citations

  • Lubricating grease composite and preparation method thereof

    CN101967417A

  • Self healing silica based dielectric ink for printed electronic applications

    WO2015087350A1

  • Spherical forsterite particles, method for producing same, and resin composition including spherical forsterite particles

    WO2020111126A1